[OP.1C.02] SPECTRAL ESTIMATION OF PETERSON'S MODULUS VARIABILITY FROM ARTERIAL BLOOD PRESSURE AND WAVELET ANALYSIS. (September 2016) - Ramirez, A.J.; Pessana, F.; Zenone, P.; Linale, N.; Sanchez, R.
Abstract : Objective: Arterial stiffness is mainly characterized by its Peterson's Modulus (EP). Increased values of EP are associated with a reduced heart function and an increased arterial blood pressure. Assessment of EP requires simultaneous measurements of arterial diameter and pressure signals. However, instantaneous determination of arterial diameter signals implies optical and ultrasonic techniques and neither of them are portables. Aims: To evaluate a novel method for estimating the Ep spectral variability of arterial stiffness, without arterial diameter signals. Design and method: Arterial pressure (Konigsberg micro-transducer) was measured in 10 sheeps (25–35 kg) during 24 hours. Instantaneous cardiac cycle of pressure signals were determined using five–level multi-resolution wavelet analysis and decomposition. A state machine processed and analysed different linear combinations of details d3, d4 and d5 of mother wavelet Symlet11. EP spectral estimation assessment involved the study of various temporal locations of the fiducial elasticity starting point within each beat. Moreover, discard criteria were added from the heart rate variability studio and coherence index between systolic pressure and beat to beat intervals around 0.1 Hz. Agreement between the actual direct measurement of EP and the proposed method of spectral stiffness estimation was analyzed according to the Bland–Altman approach. Results: Results showed a high coherence (more than 70%) between the actual and proposed method for a wide frequency range (0 to 0.5 Hz). Bland & Altman test showed a standard deviation of the mean less of 10% between the proposed methodology and the direct assessment of EP. Conclusions: The methodology presented in this work evidenced high levels of spectral coherence in EP variability studios and no significantly difference between the actual and the proposed estimation method. So, this novel method is able to estimate the Peterson's modulus spectral variability by solely using the arterial blood pressure signal.